Lying as an act of speech – a few remarks from a philosophical and legal perspective - Kołodziejczyk, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The article presents issues concerning the analysis of the nature (essence) of lies from the perspective of logical pragmatics. The conclusions were confronted with selected institutions of civil law, in order to show how law and jurisprudence perceive different forms of “lies” occurring on the basis of positive law.